Three‐dimensional microstructure of samples recovered from asteroid 25143 Itokawa: Comparison with LL5 and LL6 chondrite particles. (9th August 2013) - Tsuchiyama, Akira; Uesugi, Masayuki; Uesugi, Kentaro; Nakano, Tsukasa; Noguchi, Ryo; Matsumoto, Toru; Matsuno, Junya; Nagano, Takashi; Imai, Yuta; Shimada, Akira; Takeuchi, Akihisa; Suzuki, Yoshio; et al.
Abstract In this study, the three‐dimensional (3‐D) microstructure of 48 Itokawa regolith particles was examined by synchrotron microtomography at SPring‐8 during the preliminary examination of Hayabusa samples. Moreover, the 3‐D microstructure of particles collected from two LL6 chondrites (Ensisheim and Kilabo meteorites) and an LL5 chondrite (Tuxtuac meteorite) was investigated by the same method for comparison. The modal abundances of minerals, especially olivine, bulk density, porosity, and grain size are similar in all samples, including voids and cracks. These results show that the Itokawa particles, which are surface materials from the S‐type asteroid Itokawa, are consistent with the LL chondrite materials in terms of not only elemental and isotopic composition of the minerals but also 3‐D microstructure. However, we could not determine whether the Itokawa particles are purely LL5, LL6, or a mixture of the two. No difference between the particles collected from Rooms A and B of the sample chamber, corresponding to the sampling sequence of the spacecraft's second and first touchdowns, respectively, was detected because of the statistically small amount of particles from Room B.